Un vistazo al Derecho Constitucional a través del Derecho Internacional. Entrevista a Juan José Ruda Santolaria - Monge Morales, Gonzalo J. (2015)
What is the normative status of a treaty in Peruvian domestic law? What would happen at theinternational level if the Peruvian ConstitutionalCourt declared  a treaty to be unconstitutional? How to interpret Peruvian maritime domain, asrecognized in our Constitution, after the ruling of the International Court of Justice on the maritimedifferendum with Chile?These issues don’t only concern Constitutional Law; thus, in this interview, the renowned professor provides us with, from the standpoint of International Law, answers about these and other issues, but he also illustrates us about the implications for Peru of the aforementioned Court’sruling, delivered more than a year ago.